1997
DOI: 10.1192/pb.21.7.387
|View full text |Cite
|
Sign up to set email alerts
|

Flexible training in psychiatry

Abstract: EDITORIALSThe Royal College of Psychiatrists and the speciality of psychiatry has a long history of support for part-time or flexible training. The motivating factors for this support were a recogni tion of the demand for flexible training among the trainees themselves, a large proportion of whom were women, and an acknowledgement that psychiatry was a shortage speciality and needed to recruit and retain the best possible doctors. The College, working together with the Department of Health, was enabled to set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 2 publications
(1 reference statement)
1
13
0
Order By: Relevance
“…Flexibly trained psychiatrists have been found to outperform their full-time colleagues in terms of how quickly they gain College membership (assessed by number of examination attempts), and also gain experience in other specialties prior to psychiatry (Herzberg & Goldberg, 1999). This, coupled with a reported increase of 30% in demand for flexible training posts across specialties (Goldberg, 1997), shows that this is a crucial group for policy-makers to recognise and encourage.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Flexibly trained psychiatrists have been found to outperform their full-time colleagues in terms of how quickly they gain College membership (assessed by number of examination attempts), and also gain experience in other specialties prior to psychiatry (Herzberg & Goldberg, 1999). This, coupled with a reported increase of 30% in demand for flexible training posts across specialties (Goldberg, 1997), shows that this is a crucial group for policy-makers to recognise and encourage.…”
Section: Discussionmentioning
confidence: 96%
“…Except for some posts in Oxford, the scheme was not greatly used until 1979, when there was a focusing on senior registrar training, with a second boost in 1991 with the introduction of a new scheme for career registrars. Demand for flexible training posts is growing, with a reported increase of 30% across grades and specialties (Goldberg, 1997). It has been suggested that, nationally, 14% of psychiatrists train flexibly, although the uptake varies regionally between 3.5% and 26% (NHS Management Executive, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing demand for flexible training posts is reported nationally, with a 30% increase throughout all specialties (Goldberg, 1997). In Northern Ireland there is a waiting list for flexible training posts for specialist registrars across all specialties funded by the Northern Ireland Medical and Dental Training Agency (NIMDTA).…”
Section: Discussionmentioning
confidence: 99%
“…Goldberg (1997) reported an over 30% increase across all grades and specialities in the previous 2 years. NHS Executive figures for July 1996 showed 8% of doctors across all specialities training flexibly, with 14% training flexibly in psychiatry (of those, 45% were in the psychotherapy subspeciality and 13% in adult mental illness).…”
Section: The Way Forwardmentioning
confidence: 99%
“…Nationally, there is wide variation in the uptake of flexible training in psychiatry, ranging from 3.5 to 26% of doctors training flexibly. Goldberg (1997) and Clay (1998) suggest several reasons for this, including the availability of funding to support part-time training, reluctance of local trusts to fund the additional duty hours, degree of commitment of key people at local and regional level and demand from the trainees themselves.…”
Section: The Way Forwardmentioning
confidence: 99%